Conflicting identities: Cosmopolitan or anxious? Appreciating concerns of host country population improves attitudes towards immigrants - Tobias Stöhr; Philipp C. Wichardt (Kiel Institute for the World Economy (IfW), 2016)
Cosmopolitan or anxious? In order to test the influence of conflicting aspects of identity, German respondents were asked about their attitude towards a Syrian refugee the description of whom was varied in various domains (N=662). Once the refugee is described as being aware of as well as open towards concerns in the German population - regarding cultural change, arising costs and increasing violence - reported levels of sympathy and trust increase substantially, especially for risk averse people. Additional data from a second questionnaire (N=118) show that a German person expressing such concerns is perceived as less cosmopolitan and more likely to vote for the emergent populist right-wing. Combining these findings, we argue that acknowledging concerns of the host population relieves the tension between the anxious and cosmopolitan part of peoples' identities and, therefore, allows them to respond more openly since an aspect of identity that is acknowledged by context (expressing anxieties) has less influence on actual behavior (expressing sympathy). Apart from that, we find that personal experience and the higher willingness to take risks are important for the individual willingness to interact. Our findings highlight the importance of context, identity and individual characteristics for host populations' attitudes towards of refugees.
Keywords: F22; Z10; Z12; 330; Identity; Immigration; Integration; Migration; Refugees